A new species of Bemlos Shoemaker, 1925 (Amphipoda: Aoridae) from deep water off Tanabe Bay, Japan, with a review of the deep-sea aorids and their adaptations to the deep sea. Issue 1 (7th January 2019) - Kodama, Masafumi; Kawamura, Tomohiko
Abstract: A new species of aorid amphipod, Bemlos seisuiae sp. nov., is described from deep muddy bottom off Tanabe Bay, Japan. The new species is characterized by its conspicuously slender and elongated pereopods 3–6. The aorids reported from deep water are reviewed, and their morphological adaptations to deep water are discussed.